Strength Measurements and Results of Surgical Treatment of Complete Rectus Femoris Mid-substance Rupture: A Case Report - Kartio Anna A; Jokela Aleksi M; Valle Xavier; Pruna Ricard; Mäkelä Keijo; Lempainen Lasse L (India, 2023)
Introduction: Rectus femoris injuries are common in sports requiring sprinting and kicking, especially in football. In addition to sports injuries, rectus femoris injuries can occur during physically active daily living and physical work. Most muscle injuries heal well by conservative treatment, but more severe ruptures often require surgical treatment, especially in athletes. Some ruptures can cause so severe functional loss of the muscle that it causes problems also in everyday life. Complete rectus femoris mid-substance rupture is a rare injury type, which tends to recover poorly and cause significant functional deficit. Descriptions of this injury type are mainly lacking in the literature and there is no consensus on the management of these injuries. To the best of our knowledge, this is the first report of this kind in the literature including strength measurements pre- and post-operatively.
Case report: We report a case of a 48-year-old Caucasian man who suffered a complete rectus femoris mid-substance rupture at physically active work. The injury mechanism was slipping on an asphalt ramp, leading to rapid eccentric contraction of rectus femoris involving knee flexion and hip extension. The rupture was treated surgically and the muscle strength of quadriceps femoris was measured pre- and postoperatively.
Conclusion: This case report showed that muscle strength in knee extension recovers well after an operative treatment of complete rectus femoris mid-substance rupture. Therefore, it can be concluded that operative treatment is beneficial for this specific injury type. This case report brings important and objective evidence on the relevance of surgical treatment in these injuries that are mainly lacking the consensus about the best treatment methods. To the best of our knowledge, this case report is also the first one which indirectly shows the value of isolated rectus femoris muscle in the whole quadriceps muscle group.